Keratosis Follicularis Spinulosa Decalvans in a female child- a rare presentation - Chowdhury, Joyeeta; Ghoshal, Loknath; Bannerjee, Saikat (Bangladesh Journal of Medical Science, 2017)
Congenital alopecia universalis is a very rare presentation. A 6 year old girl came to us with total alopecia and multiple horny keratosis pilaris like skin lesions all over the body. The alopecia was mostly non-scarring with a few patches of scarring over the scalp. Histology from scalp revealed follicular plugging with perifollicular infiltrate of lymphocytes and plasma cells. The case was diagnosed as Keratosis follicularis spinulosa decalvans. This is very rare and even rarer in females. Bangladesh Journal of Medical Science Vol.16(4) 2017 p.591-593